Virtual Classes in a Non-native Language during the Year of the Pandemic: Confidence and Critical Thinking as Basis of Academic Integrity - Jeikner, Alexandra (Canadian Perspectives on Academic Integrity, 2021)
Introduction. This presentation will focus on teaching academic writing and research at the American College of Greece, using English as the language of instruction, to students whose native language is in the majority not English on challenges, during the time of the pandemic. The proposition is made that the move from physical classes to virtual ones might have enhanced challenges but also helped identify useful techniques that can inspire students to become more involved in their studies as well as to perceive academic integrity as valuable. For sure, for students, attendance at an institution that promises a degree in a non-native language grants a competitive edge in the job market as it stands for linguistic competence in addition to subject expertise – but it is exactly that which also places students under increased stress. This stress is particularly exacerbated when secondary education tends to promote rote learning and discourage critical thinking. High school students that enroll at a university with such a learning base often feel overwhelmed, even threatened, when asked to engage with complex concepts and express critical ideas; even more so to understand and express these ideas in a foreign language. Some students experience frustration which in turn leads them to give up – while some others, as a last resort, turn to a ghost writer for help so as not to fail. In the physical classroom, with students producing in-class work, a professor has the advantage of being familiar with a student’s language competencies and thus being able to identify uncharacteristic work, but now, in the virtual classroom, certainty of originality is more difficult. The presentation will describe a number of techniques that proved useful during this last year when all classes were virtual. As such, it can be considered a collection of observations transformed into a case study. Overall, what was observed was that while existing and well-known techniques to curb and identify breaches of academic integrity such as plagiarism continued to work, with more or less the same success as in the physical classroom, new techniques were needed to inspire critical engagement, participation and pride in own work, thereby steering students away from academic dishonesty in the form of contract cheating. Objective. This presentation aims to share these insights with others in the academic field and to encourage dialogue so to allow for the emergence of best practice strategies. It would be particularly of interest to hear from other instructors who teach in settings where the language of instruction is not the students’ native language, as to how students are encouraged to engage, participate and also to display academic honesty.